Role of the hippocampus in contextual memory after classical aversive conditioning in pigeons (C. livia) - Reis F.; Schenka A.A.; Melo L.L.; Ferrari E.A.M. (Brazilian Journal of Medical and Biological Research, 1999)
We investigated the effects of hippocampal lesions with ibotenic acid (IBO) on the memory of the sound-context-shock association during reexposure to the conditioning context. Twenty-nine adult pigeons were assigned to a non-lesioned control group (CG, N = 7), a sham-lesioned group (SG, N = 7), a hippocampus-lesioned experimental group (EG, N = 7), and to an unpaired nonlesioned group (tone-alone exposure) (NG, N = 8). All pigeons were submitted to a 20-min session in the conditioning chamber with three associations of sound (1000 Hz, 85 dB, 1 s) and shock (10 mA, 1 s). Experimental and sham lesions were performed 24 h later (EG and SG) when EG birds received three bilateral injections (anteroposterior (A), 4.5, 5.25 and 7.0) of IBO (1 µl and 1 µg/µl) and SG received one bilateral injection (A, 5.25) of PBS. The animals were reexposed to the training context 5 days after the lesion. Behavior was videotaped for 20 min and analyzed at 30-s intervals. A significantly higher percent rating of immobility was observed for CG (median, 95.1; range, 79.2 to 100.0) and SG (median, 90.0; range, 69.6 to 95.0) compared to EG (median, 11.62; range, 3.83 to 50.1) and NG (median, 7.33; range, 6.2 to 28.1) (P<0.001) in the training context. These results suggest impairment of contextual fear in birds who received lesions one day after conditioning and a role for the hippocampus in the modulation of emotional aversive memories in pigeons.